Debiasing a decision maker facing supply uncertainties in a newsvendor setting - ZELLER, Alan William (Institutional Knowledge at Singapore Management University, 2021)
Companies must be prepared to manage uncontrollable events that will disrupt their supply chain and add uncertainty to their inventory models. This thesis first studies the effect of different types of supply disruption risks on the ordering performance of profit-maximizing decision makers in a newsvendor setting. Then, this thesis aims at extending the literature on the newsvendor model in studying the effect of a Decision Support System and the effect of a Secondary Task on the ordering performance of profit-maximizing decision makers who face supply uncertainties in a newsvendor setting. Finally, implications for scholars and practitioners are discussed.